Empathy with Patients Compared between First and Final Year Nursing Students - Solmaz Saeidi; Shadman Reza-Masouleh; Minoo Mitra Chehrzad; Ehsan Kazem Nejad Leili (Guilan University of Medical Sciences, 2017)
Introduction: Patient-nurse relationship has been recognized as the key factor in nursing practice. Considering the importance of professional relationship in nursing discipline, and especially empathy and its professional role, the need to address this phenomenon in nursing education in Iran is profoundly felt. Objective: The present study was conducted with the aim to compare level of empathy with patients and related factors between first- and final-year nursing students of Guilan University of Medical Sciences. Materials and Methods: The present descriptive-analytical study was conducted on 180 nursing students of Guilan University of Medical Sciences (ShahidBeheshti School of Nursing and Midwifery in Rash and Langrood) selected by census from the academic year 2014-15. Data collection tool was a two-part questionnaire consisting of socio demographic data details and Jefferson Scale of Empathy containing 20 items, scored according to Likert scale from strongly agree (7 points) to strongly disagree (1 point), in which students chose items based on the level their agreement. Students' mean empathy score was calculated from maximum seven points (higher empathy) and minimum one point (lower empathy). In total, the maximum score for the 20 items was 140 points and minimum 20 points. Data thus collected were analyzed using descriptive and analytical statistical tests (independent t, Pearson s correlation coefficient and logistic regression). Results: Students' mean age was 22.21±2.94 years, and the majority were female (63.3%). No significant difference was observed between empathy among first-year students (5.03±0.041) and final-year students (4.94±0.7) (P<0.28). Students' empathy was found significantly related to interest in nursing discipline (P<0.001), student work (P<0.012), and mother's education below diploma (P<0.032). Among study variables, interest in nursing discipline (P<0.001), father's education (P<0.009), and history of hospitalization (P<0.046) were factors predicting level of empathy, such that, students who were interested in nursing discipline compared to those that were not had higher levels of empathy (β=0.392). Also, students with history of hospitalization had a higher level of empathy (β=0.2). Regression test results showed that level of empathy diminished with a higher level of father's education (β=-0.142). Conclusion: The results obtained showed no significant difference between first- and final-year students in terms of empathy score. Since reinforcing predicting factors leads to greater student empathy with patients, empathy skills education in the course of study and generating interest among students appears to increase their sense of empathy